2017
DOI: 10.35791/agrsosek.13.3a.2017.18401
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Penyebab Putus Sekolah Dari Anak Petani Dan Non-Petani Di Desa Sea Dan Desa Warembungan Kecamatan Pineleng Kabupaten Minahasa

Abstract: This study aims to determine what factors are the cause of drop out of the children of farmers and non-farmers and whether there are differences in factors that cause drop out of the children of farmers and non-farmers. The analysis used in this research is by using descriptive analysis. This study was conducted from April to June 2017. This study used primary data and secondary data. Primary data was collected by direct interviews based on list of questions that have been prepared to the total respondents as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
0
0
3
Order By: Relevance
“…Peer relationships that deviate or behave negatively play an important role in developing antisocial behavior in adolescents (Mahoney, 2018;Mccaffrey et al, 2010) The research results from the fourth informant found that he had friends outside of school who were older and no longer in school. Having friends in a bad social environment is another factor in developing the intention to drop out of school in adolescents because teenagers will be affected by the behavior and mindset of children who have dropped out of school earlier (Gao et al, 2019;Mua et al, 2017).…”
Section: The Relationships With Peersmentioning
confidence: 99%
“…Peer relationships that deviate or behave negatively play an important role in developing antisocial behavior in adolescents (Mahoney, 2018;Mccaffrey et al, 2010) The research results from the fourth informant found that he had friends outside of school who were older and no longer in school. Having friends in a bad social environment is another factor in developing the intention to drop out of school in adolescents because teenagers will be affected by the behavior and mindset of children who have dropped out of school earlier (Gao et al, 2019;Mua et al, 2017).…”
Section: The Relationships With Peersmentioning
confidence: 99%
“…Berdasarkan hasil penelitian yang dilakukan oleh Fatah, Suhaili, dan Farida (2021), tingkat partisipasi pendidikan semakin menurun seiring naiknya jenjang pendidikan. Fenomena ini kemungkinan besar disebabkan ketidakmampuan untuk melanjutkan pendidikan ke jenjang yang lebih tinggi akibat faktor biaya, kesadaran akan pentingnya pendidikan, serta faktor lingkungan (Mua, Manginsela and Baroleh 2017). Permasalahan menurunnya minat masyarakat di setiap kenaikan jenjang pendidikan ini patut mendapatkan prioritas perhatian dari pemerintah.…”
Section: Program Pemerintah Yang Mendukung Pembangunan Kepemudaan DI ...unclassified
“…Keluarga petani merupakan sistem yang menjalankan berbagai fungsi keluarga, seperti fungsi ekonomi dan pengasuhan pada anak (Laa, 2018). Fungsifungsi yang dijalankan petani sebagai orang tua akan berdampak pada proses pendidikan anak-anak dalam keluarga tersebut (Rahayu, 2014;Musrah, 2016;Mua, Manginsela and Baroleh, 2017;Anpersya and Wirdanengsih, 2020). Meskipun ada yang mengungkapkan bahwa tingkat pendidikan petani tersebut tidak berpengaruh pada tingkat pendidikan anakanaknya (Dayat, Anwarudin and Makhmudi, 2020), tetapi menurut Santoso, dkk ( 2020) tingkat pendidikan, baik formal maupun informal, berpengaruh nyata terhadap percepatan regenerasi petani.…”
Section: Dilema Pendidikan Tinggi Petani Mudaunclassified
“…Namun, ada petani yang merasa pendidikan tidak terlalu penting karena hanya berujung pada mencari kerja yang sebenarnya bisa langsung dilakukan di sektor pertanian tanpa menempuh proses pendidikan tinggi (Musrah, 2016). Intervensi dari orang tua tersebut, ditambah dengan kondisi ekonomi yang kurang memadai sering menjadi alasan dibalik kejadian putus sekolah di antara anak-anak petani (Anshar and Syukur, 2016;Mua, Manginsela and Baroleh, 2017). Dalam suatu penelitian di suatu desa, fenomena putus sekolah anak yang berasal dari keluarga petani ditemukan mencapai 70% (Pranata, 2018).…”
Section: Dilema Pendidikan Tinggi Petani Mudaunclassified